2008
DOI: 10.1016/j.engstruct.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between experimental tests and numerical simulations carried out on a tensegrity minigrid

Abstract: To cite this version:Jean-François Dubé, Nicolas Angellier, Bernard Crosnier. Comparison between experimental tests and numerical simulations carried out on a tensegrity minigrid. Engineering Structures, Elsevier, 2008, 30, pp.1905-1912 -mail: dube@lmgc.univ-montp2.fr, angellier@lmgc.univ-montp2.fr, crosnier@lmgc.univ-montp2.fr AbstractTensegrity systems are structures in equilibrium under an initial self-stress state. This self-stress state is composed of elementary self-stress states, which constitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
1
8
1
Order By: Relevance
“…Moussa et al (2001) showed that the fundamental modes of simplex type modules are those corresponding to internal mechanisms and proposed a direct relation between self-stress and first natural frequency. Dubé et al (2008), for a tensegrity minigrid, as well as Tibert and Pellegrino (2003), for a deployable tensegrity mast, obtained similar results.…”
Section: Analytical Formulationsupporting
confidence: 85%
See 1 more Smart Citation
“…Moussa et al (2001) showed that the fundamental modes of simplex type modules are those corresponding to internal mechanisms and proposed a direct relation between self-stress and first natural frequency. Dubé et al (2008), for a tensegrity minigrid, as well as Tibert and Pellegrino (2003), for a deployable tensegrity mast, obtained similar results.…”
Section: Analytical Formulationsupporting
confidence: 85%
“…Masic and Skelton (2006) used a linearized dynamic model to enhance the dynamic control performance of a tensegrity structure. Dubé et al (2008) presented a comparative study between experimental tests and numerical simulations carried out on a tensegrity minigrid considering static as well as dynamic loading. Recently, Tan and Pellegrino (2008) investigated the nonlinear vibration of a cable-stiffened pantographic deployable structure and showed that the system resonant frequencies are related to the level of active cable pretension.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the effective measurement of the self-stress state of a tensegrity structure is treated by Dubé et al (2008), using direct and indirect measurement methods. The monitored structure consists of a tensegrity minigrid featuring 24 struts and 57 cables.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tensegrities have some unique features that result from the infinitesimal mechanisms, which are stabilized by self-stress forces. It is possible to control their static and dynamic properties by adjusting the pre-stressing forces [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%